Teachers’ Strategies in Developing Istima’ (Listening) Skills in Arabic Language Learning at Madrasah Aliyah: A Descriptive Qualitative Study - Dede Usman; Ade Arip Ardiansyah; Faiza Geovani El Fikri; Hamidatul Sa’diyah (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to identify the strategies used by teachers to develop istima’ (listening) skills, the supporting and inhibiting factors in the development of these skills, and the efforts made by teachers to overcome obstacles in enhancing students’ istima’ abilities at Madrasah Aliyah. The research employs a descriptive qualitative approach to provide an in-depth description of teachers’ strategies in developing listening skills. Primary data were obtained through interviews, observations, and documentation, while secondary data were sourced from relevant literature and learning documents. Data collection was carried out using triangulation techniques. The analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing, to produce a comprehensive understanding of teaching practices and their supporting factors. The results reveal that the development of istima’ skills at Madrasah Aliyah is conducted through audio-based, visual-based, collaborative, and technology-assisted strategies tailored to students’ needs. The success of these strategies is influenced by adequate media, a conducive learning environment, and student motivation. However, obstacles remain, such as limited teacher competence, insufficient facilities, and students’ low vocabulary mastery. Therefore, teachers need to be creative, utilize technology, strengthen mufrodat (vocabulary), and collaborate integratively with students and the institution.